CONTRIBUTION OF MAHMUD YUNUS ISLAMIC EDUCATION LEARNING METHOD IN AL-TARBIYAH WA-ALTA’LIM BOOK - Zulfikar Ali Buto (UIN Sumatera Utara Medan, 2019)
Mahmud Yunus’ contribution to the development of learning methods has poured in a bookentitled al-Tarbiyah wa al-Ta’lim. The bookprovides inspiration to researchers to conduct critical analysis of analysis figures. This study aimed to see the contribution of learning methods of Islamic Religious Education Mahmud Yunus in the book al-Tarbiyah wa al-Ta’lim. This research used qualitative research with the character study approach. The findings of contribution of learning method of Islamic Education Mahmud Yunus such as al-Istiqraiyah learning method, al-Tatbiqiyah learning method, al-Khabariyah learning method, and al-Tahawuriyah learning method Mahmud Yunus was able to develop the learning process in the five stages of the learning process. These five stages include al-Ta’aruf, Muqaddimah, al-‘Arad, al-Tatbiq, and al-Ikhtitam.